Design an Interactive System for Construction the Cold Rolling Line (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Thermal expansion of rolled material can threaten the mechanical dimensions if they are heated, this heat can softening the metal. Aluminum cold rolling strips are reduced to tight mechanical tolerances. Strips below the critical temperature run faster without loss any properties of metal. Due to friction between metal and rolls, metals suffer high compressive stresses through operation until the final product. Products of cold rolling are with high surface finishing and good mechanical properties. Cold rolling assist to close product dimensions. We are modeling the cold rolling mill by studying all factors affected and relations between them, so we improved the mill productivity with high quality and low loss scrap for products. We are also scheduling the cold rolling process to reach the optimal throughput.